PENGARUH MUQASHSHA DALAM PIUTANG MURABAHAH TERHADAP PENDAPATAN BAITUL QIRADH BINA INSAN MANDIRI BANDA ACEH - JUNITA, IRNI (State Islamic University (UIN) Ar-Raniry, 2016)
This paper aimed to investigate the influence of muqashsha in murabaha credit on the revenue of Baitul Qiradh Bina Insan Mandiri Banda Aceh. The results showed that the muqashsha’s influence in Murabaha credit included the reduced amount of the annual revenue set at the beginning whenever the customer made accelerated payment, and every customer who made the acceleration of repayment before the due date of the murabaha product would get muqashsha with discounted price of 60% of the residual margin available. There are two factors causing the customer to make accelerated payment. First, they have sufficient or more funds. Second, they want to return it because they wish to take the next financing. In Baitul Qiradh Bina Insan Mandiri, the muqashsha was provided because most customers intended to make accelerated repayment in order to take the next financing. In this regard, good working relationship could be established between the customers and Baitul Qiradh Bina Insan Mandiri. In addition, the customers also obtained the benefits due to the acceleration of repayment of the muqashsha.